ANALISIS BUTIR ESAI 10-ITEM PADA KELAS XI SMA MUHAMMADIYAH BATUDAA 2025/2026 - Konijo, Nur'Ain Pratami A.; Machmud, Tedy; Rahmi, Emli (Universitas Bhinneka PGRI, 2025)
In the 2025–2026 academic year, this research is to assess the quality of the math exam problems on the subject of three-variable linear equation systems in the interactive e-book for grade XI at SMA Muhammadiyah Batudaa that is based on infographics. Four primary factors were examined in the evaluation: the degree of difficulty, validity, dependability, and discriminating power. Student response sheets from a ten-question essay test served as the data source for the quantitative descriptive methodology. Twenty-seven XIA students served as the study's subjects. 50% of the questions had strong discriminating power, 10% were sufficient, 30% were poor, and 10% were extremely poor, according to the analysis's findings. Thirty percent of the questions were categorized as easy, sixty percent as moderate, and ten percent as challenging. According to validity analysis, half of the items were deemed valid and the other half were deemed invalid. The instrument has strong internal consistency, as indicated by the reliability test findings using the Cronbach's Alpha formula, which produced a coefficient value of 0.803, falling into the very high range. These results suggest that although incorrect or ineffective questions should be changed or replaced, valid and high-quality questions should be added to the question bank. To guarantee fair and accurate assessment quality, regular evaluation and instrument trials are strongly advised.